Demystifying second hand car market in Bangladesh using multimodal machine learning techniques - Islam, Roman; Rahman, Arman; Rahman, Asifur; Ferdous, Wasiq; Arman, Sk.MD.Golam (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.